Learning activity: its contribution to the development of theoretical thinking of children at school - Mame, Osvaldo Augusto Chissonde; Miguel, José Carlos [UNESP]; Miller, Stela [UNESP] (Universidade Estadual de Maringa, 2020)
The purpose of this article is to analyze the contribution of learning activity to the development of theoretical thinking of the child from the first years of elementary school, a period previous to early childhood education in which the child, by means of the activity that promotes his development, social role-play, begins to take the first steps of the formation of his personality. The child's entry into school provides conditions for him to develop his psyche, now through learning activity, directed by the teacher through his intentionally programmed teaching activity to drive student learning. This movement concretizes the change of the main activity of the small child to the main activity of the schoolchild, that is, from the social role-play to learning activity that governs the most important changes in the psychic processes and in the psychological traits of the child's personality in school age. The learning activity proposes to develop theoretical thinking through scientific concepts as opposed to teaching that promotes students' empirical thinking. This article derives from qualitative research, based on a bibliographical basis, with reference to a set of authors, psychologists and psychopedagogues, of the Cultural-Historical Theory and Developmental Teaching, whose works express the objectification and orientation of a school that is committed to integral and human development of children and whose theoretical matrix is dialectical and historical materialism. The research carried out allows us to affirm that an organized education to develop learning activity in the children promotes the conditions to develop their theoretical thinking and assimilate the scientific knowledge.
Actividad de estudio: su contribución al desarrollo del pensamiento teórico en escolares
Atividade de estudo: sua contribuição para o desenvolvimento do pensamento teórico da criança em situação escolar
Keywords: concept formation; education; elementary education; main activity; organization of educational practices; teaching-learning process